Dysfunction of the ventriculoperitoneal shunt device following magnetic resonance imaging: a case report - Ismail Bozkurt; Kivanc Yangi; Jack Wellington; Manuel De Jesus Encarnación Ramirez (Egyptian Journal of Neurosurgery)
Abstract Background Ventriculoperitoneal shunting is a standard tool in treating patients with hydrocephalus. With advanced shunting systems and easy-to-reach imaging techniques, straightforward surgery usually alleviates the symptoms of carefully selected patients. Nonetheless, its follow-up and common complications create an encumbrance for surgeons. Case presentation A 64-year-old woman presented with a headache, cognitive decline, and urinary incontinence. She was diagnosed with idiopathic normal pressure hydrocephalus. She underwent six revision surgeries for shunt-related and unrelated complications throughout 2 years. Notably, shunt dysfunction was observed even after the placement of an MRI-compatible valve. She continues to follow up on her controls with no significant symptoms. Conclusions In this case, we report our experience with a hydrocephalic patient who underwent multiple shunting surgeries with numerous complications. Selecting the proper valve and managing a vast entity of complications is a complex process. Most notably, the interaction of valves with electromagnetic fields should be cautiously monitored.